Effectiveness of Different Volumes of Articaine for Inferior Alveolar Nerve Block for Mandibular Molar Teeth with Symptomatic Irreversible Pulpitis - Muhammad Umair, Mohammad Tahir, Syed Abdul Rauf Shah, Muhammad Athar Khan, Syeda Rabia Rahat Geelani, Hamza Ulfat (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective of this study was to determine which of two different volumes of articaine is more efficient for performing an inferior alveolar nerve block (IANB) in the treatment of symptomatic irreversible pulpitis in molars. Study Design: Randomized Study Place and Duration: Foundation University School of Health Sciences, Islamabad and Dental Department, DHQ Teaching Hospital DI Khan, KPK from May, 2022 to April, 2023. Methods: Total 94 patients had mandibular molar teeth with symptomatic irreversible pulpitis were included. After obtaining informed written consent detailed demographics of enrolled cases included age, sex, type of molars and education status were recorded. 47 mandibular molar teeth received 2 cartridges (3.6 mL) of 4% articaine in group I and 47 cases of group II received 1 (1.8 mL) of 4% articaine. We used a Heft-Parker visual analog scale to record their levels of discomfort prior to, during, and after access cavity preparation and root canal instrumentation. If the anaesthetic only dulled the pain, it was a success. The t-test and the chi-square test were used to assess the data. Results: There were majority 59 (62.8%) males and 35 (37.2%) females in our study. The included patients had mean age 30.21±16.58 years. Majority of the cases had first molars 55 (58.5%) and 39 (41.5%) cases had second molars. Total 43 (45.7%) cases were educated and 51 (54.3%) cases were non educated. Although neither group achieved 100% success with their anesthetic, we found that 3.6 mL articaine resulted in a considerably greater success rate for IANBs (39, 82.97%) than 1.8 mL of the same amount of anesthetic solution (17, 36.2%) (P <0.003). We found a significantly reduction in pain score (HP VAS)1.19±5.37 as compared to group II 3.6±7.17 with p value <0.004. Conclusion: In our research, we found that increasing the volume of articaine greatly improved the success rate of IANBs in teeth with symptomatic irreversible pulpitis in the mandibular molars, but did not guarantee complete anesthetic success in all cases. Keywords: Articaine, inferior alveolar, Anesthesia, mandibular molar, nerve block, irreversible pulpitis, symptomatic